Radium-Derived Water Mixing and Associated Nutrient in the Northern South China Sea - Liu, Jianan; Du, Jinzhou; Wu, Ying; Liu, Sumei (Frontiers in Marine Science, 2022)
Nutrients play an important role as biogenic elements in modulating marine productivity, and water mixing usually facilitates the transportation of nutrients in the coastal ocean. In this study, the distributions of naturally occurring radioisotopes 226Ra and 228Ra in the surface and water column of the northern South China Sea (NSCS) have been investigated to estimate oceanic mixing and nutrient supplies. We identified three masses of the South China Sea Warm Current (SCSWC), the South China Sea Branch of the Kuroshio (SCSBK), and shelf water in the summer of June 2015, but only SCSWC and SCSBK were observed in the spring of March 2017. The fraction of the SCSBK in summer was estimated to be an average of 0.25 ± 0.16, which was lower than that in the spring of 0.57 ± 0.32 in our study area. The horizontal mixing from the Pearl River plume revealed eddy diffusion of (1.2 ± 0.79) × 105 cm2/s and advection velocity ω of 0.25 ± 0.16 cm/s in the slope region. In the water column, the best-fit exponential curve gradient of 228Ra led to a vertical diffusion coefficient of 0.43 ± 0.33 cm2/s that went down to the subsurface of the upper 1,000 m, and an upward vertical diffusion coefficient was revealed as 18 ± 9.9 cm2/s from the near-bottom. Combining the nutrient distributions, horizontal mixing from the Pearl River plume carried (5.6 ± 4.9) × 102 mmol N/m2/d, 2.2 ± 2.0 mmol P/m2/d, and (4.1 ± 3.9) × 102 mmol Si/m2/d in the very surface layer, suggesting that shelf water plays a significant role in the nutrient sources of the slope of the NSCS during June 2015. The upward vertical mixing supplied 2.7 ± 1.6 mmol N/m2/d, 0.18 ± 0.11 mmol P/m2/d, and 15 ± 8.4 mmol Si/m2/d to the upper layer, which appeared more important than atmospheric deposition and rivaled submarine groundwater discharge.